Balanced scorecard at the Royal Library, Copenhagen - Krarup, Karl (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
The Royal Library is the national library of Denmark and University Library for Copenhagen University. In 2000 the Royal Library started using Balanced Scorecard as an instrument for creating a better connection between its day to day activities and its strategic goals. The Royal Library has a number of goals in choosing the Balanced Scorecard. Important goals are: • to develop a strategic instrument which can be used to represent the strategic goals of the library in such a way that we can measure how close our actual performance comes in reaching these goals • to create an instrument which can be used in negotiating the goals and performance of the departments in such a way that the department leaders keep a fair level of autonomy in running the departments and give the institution leader a good overview of the actual performance • to make the individual department’s contribution to the institutional performance explicit to personnel and leaders • to formulate and monitor important strategic areas of the library’s development to support steering the development • to make the library and its performance more transparent to all interested actors in the library The article presents the main issues in developing the library’s use of the Balanced Scorecard. It includes a number of concrete cases from the implementation of the method and its use as a strategic instrument in monitoring and developing the Royal Library as a library growing more digital and hybrid. To increase the digital part of its content, its services and its internal processes is among the library’s major strategic goals.